Revision of Triassic Stratigraphy of the Scoresby Land and Jameson Land Region, East Greenland. - Perch-Nielsen, K.; Birkenmajer, K.; Birkelund, T.; Aellen, M. (Meddelelser om Grønland, 1974)
A revised stratigraphic scheme is presented for the Triassic rocks between Kong Oscars Fjord and Scoresby Sund, East Greenland. The Triassic succession is described as the Scoresby Land Group comprising four formations. The lower two formations (Wordie Creek Formation and Pingo Dai Formation) belong to the Nordenskiold Bjerg Subgroup, while the upper two formations (Gipsdalen Formation and Fleming Fjord Formation) belong to the Kap Biot Subgroup. The total thickness of the Triassic sequence attains 1000 to 1500 m of which less than half is composed of marine sediments. The remainder consists of continental deposits and includes red-beds with an important evaporite complex in the middle of the succession.